2017
DOI: 10.1080/09593330.2017.1337816
|View full text |Cite
|
Sign up to set email alerts
|

Long-term operational studies of lab-scale pumice-woodchip packed stormwater biofilters

Abstract: The performance of three pumice-woodchip packed stormwater biofilter (PWSWBF) systems with three packing volume ratios of pumice to woodchip (1:2, 1:1 and 2:1) were compared. The results show that the PWSWBF system packed with a lower percentage of woodchip attained a higher removal efficiency of TCOD, TN, NH-N and TP, whereas all three systems completely removed nitrate. The highest removal efficiencies for TCOD, TN, NH-N, NO-N and TP were 95%, 70%, 86%, 100% and 100%, respectively. In the biofilter with a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Sand is a commonly used filter material (FAWB, 2009;Fassman et al, 2013;Tirpak et al, 2021), compost amendment (Fassman et al, 2013 and a submerged zone (Blecken et al, 2009;Zinger et al, 2013) has been evaluated internationally. The implementation of biochar and (to limited extend) pumice has received increasingly interest (Mohanty et al, 2018;Cheng et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sand is a commonly used filter material (FAWB, 2009;Fassman et al, 2013;Tirpak et al, 2021), compost amendment (Fassman et al, 2013 and a submerged zone (Blecken et al, 2009;Zinger et al, 2013) has been evaluated internationally. The implementation of biochar and (to limited extend) pumice has received increasingly interest (Mohanty et al, 2018;Cheng et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Mohanty et al (2018) concluded that biochar can have both positive and negative impacts on P removal rates and hence, the P removal rate was assumed to be unaffected by biochar. When pumice was used as a component in the filter material, the P removal was enhanced (Cheng et al, 2017).…”
Section: Phosphorus Removalmentioning
confidence: 99%
“…Waste is certainly a cheap and widely available material. The possibility of using some waste materials, e.g., used tires [34][35][36][37][38], acrylonitrile butadiene styrene (ABS) from waste electrical and electronic equipment [39], straw [40][41][42] and wood [40,43], as a substrate for biofilm formation has been investigated in the literature. Attempts have also been made to test textile materials, which are not classified as waste materials, as packing elements, e.g., cotton fabric [44] and polyester non-woven fabric [45].…”
Section: Introductionmentioning
confidence: 99%
“…As a low cost material, pumice has been used as a potential alternative material for pollutant removal from wastewater. Using the laboratory scale, Cheng et al (2018) examined the use of pumice-woodchip packed stormwater biofilter (PWSWBF) for pollutant removals from livestock farm stormwater. The results showed that the PWSWBF had high removal efficiency for TCOD (95%), TN (70%), NH 4 -N (86%), NO 3 -N (100%) and TP (100%), indicating that the presence of pumice significantly affect the removal of pollutants.…”
Section: Introductionmentioning
confidence: 99%